Hypokalemia and Hyponatremia in Hepatic Encephalopathy and Its Distribution Across Age, Gender, and Grade of Hepatic Encephalopathy: Hypokalemia and Hyponatremia in Hepatic Encephalopathy - Iqbal, Tamoor (Pakistan Journal of Health Sciences, 2026)
Hepatic encephalopathy is a complication of cirrhotic liver disease precipitated by a variety of factors. One such factor is disturbance in the levels of sodium and potassium. Objectives: To determine the prevalence of hypokalemia and hyponatremia in patients of hepatic encephalopathy at a secondary care setting and its distribution in different age groups, gender, and grades of hepatic encephalopathy. Methods: This cross-sectional descriptive study with stratified analysis was held at the Department of Medicine, Tehsil Headquarter Hospital, Sarai Alamgir, Pakistan, from January 2024 to February 2025. In this study, a total of 127 patients who presented with hepatic encephalopathy were included. All these patients were assessed for the presence of hypokalemia and hyponatremia. Results: Mean age of hepatic encephalopathy sufferers was 50.64 ± 10.29 years. There were 87 (68.50%) male and 40 (31.50%) female patients. The most common cause of cirrhotic liver disease was the hepatitis C virus found in 62 (48.80%) patients. Prevalence of hypokalemia and hyponatremia in HE patients was 24 (18.90%) and 49 (38.60%), respectively. There was no significant difference in the prevalence of hypokalemia in age groups (p=0.609), gender (p=0.482), or grades of hepatic encephalopathy (p=0.902). Hyponatremia was significantly higher in older people (p=0.005) while there was no significant difference in its prevalence based on gender (p=0.824) or hepatic encephalopathy grade (p=0.621). Conclusions: Hypokalemia and hyponatremia are highly common in patients with hepatic encephalopathy presenting at a secondary care hospital.